An Energy-Efficient Key Predistribution Scheme for Secure Wireless Sensor Networks Using Eigenvector. (4th June 2013) - Choi, Sung Jin; Kim, Kyung Tae; Youn, Hee Yong
Abstract : Currently, sensor networks are widely used in various fields. Here secure operations are required for critical applications since the damages are significant if the network is compromised or disrupted. For the security of wireless sensor network, the earlier schemes typically employ asymmetric cryptography. These schemes are, however, often unsuitable for wireless sensor network due to the limited computational power and energy of the sensor nodes. To address this issue, various approaches have been developed, and the random key predistribution approach has been recognized as an effective approach. One shortcoming, however, is that a common key is not guaranteed to be found between any two nodes wanting to communicate. This paper proposes a new robust key predistribution scheme solving this problem, with which the security is not compromised even though the data exchanged between the nodes are tapped by an adversary. This is achieved by using the keys assigned based on the notion of eigenvalue and eigenvector of a square matrix of a pool of keys. Mathematical analysis and computer simulation reveal that the proposed scheme significantly reduces the overhead required for secure connectivity and energy consumption of sensor nodes compared to the existing approaches.